Emergent issues in the field of drug abuse - Levy, Judith A.; Stephens, Richard C.; McBride, Duane C. (JAI, 1999)
This is the eighth volume in a series dedicated to publishing current research and conceptual papers in the broad-ranging area of the sociology of health.
Keywords: Drug abuse.; Drug abuse -- Social aspects.; Drug abuse -- Treatment.; Public health & preventative medicine.; Health systems & services.; Social Science -- General.; elektronické knihy; electronic books